Influence of bisoprolol and nebivolol on the spectrum of substituted amino acids in blood plasma of patients with stable angina - Bogdan, T.V. (Доповіді НАН України, 2021)
For many years, β-blockers have been used to treat patients with coronary heart disease. In patients with stable angina, the effect of β-blockers on the amino acid spectrum of blood serum has been studied. Its violation is considered as one of the pathogenetic links in the development of atherosclerosis. The study showed a more efficient action of nebivolol compared to bisoprolol on the amino acid imbalance. In patients with stable angina against the background of antianginal therapy, which included bisoprolol and nebivolol, there was a significant decrease in the total amount of amino acids, the amount of essential amino acids, and the amount of essential amino acids compared to the treatment. Against the background of the nebivolol treatment, there is a positive dynamics of sulfur-containing amino acids (methionine level was maintained, taurine level was significantly increased, cystine level was normalized), isoleucine level was normalized, which indirectly indicates cardioprotective and angiprotective effect of nebivolol.